Morphometric and Genetic Characterization of Honey Bees (Apis mellifera L.) From Thrace Region of Turkey - Özdil Fulya; Oskay Devrim; Işık Raziye; Yatkın Selen; Aydın Abdurrahman; Güler Ahmet (Journal of Apicultural Science, 2022)
A detailed morphological and genetic characterization of honey bees from the Thrace and west Anatolian regions of Turkey was surveyed. A total of 1650 worker bee samples (110 colonies) were evaluated with the forty-one morphological characters and 217 honey bee samples were analyzed via DNA sequencing of the tRNAleu-cox2 region. In this study, three different populations, Thrace (Tekirdağ, Kırklareli and Edirne provinces), Island Gökçeada, and western Anatolia were formed based on morphometrics, since the Marmara Sea has taken a very strong barrier role in this formation. The morphological similarity of the Thrace population was supported by the genetic analysis. The sequencing of the tRNAleu-cox2 region revealed twenty-two different haplotypes, sixteen of which are novel. The C2d, macedonica-like haplotype, was the most widely found haplotype (48%) all around the Thrace region. Along with the C2d haplotype, previously published C2s, C2v, C2i, C2j, and C2h haplotypes, and the newly found haplotypes were also observed but less frequently. In this study, Thrace honey bees were found to more similar to A. m. macedonica through the mtDNA sequence analysis, whereas carnica-like honey bees were only found near the Istranca mountain ridges, Kırklareli province and macedonica-like honey bees all around the Thrace region. According to our results, some of the Thrace honey bee populations may be both A. m. carnica and A. m. macedonica but the assignment to the latter subspecies seems more likely due to its geographic range.